Review On The Role Of Host Immune Response In Protection And Immunopathogenesis During Entamoeba Histolytica - Hassani ALSalami, Eman; Hussein Albu_Saabar, Shaymaa Rahim; Najm Abed, Hussein (Medical Science Journal for Advance Research, 2022)
Background: A protozoane parasite callede Entamoeba histolyticae (Eh) infects Entamoebae histolytica (Eh), a protozoane parasite that causese 100,000 deaths per year frome amebic dysentery and/or livere abscess, has infectede 10% of the entire world'se population. Usuallye, this extracellular parasitee colonizes the colone with high affinity bindinge to MUC2 mucin without causing illness symptoms, but occasionally, Eh invades the colonic mucosae and triggers an agressivee inflammatory responsee. The particulare host-parasite variables requirede for illnesse etiologye are still mostlye unknown. The parasite's cysteine proteasee cleaved thee C-terminus ofe MUC2, that causese the mucus layer to dissolve, followede by adsorption and cytotoxicitye of the mucosal epitheliume, are the disease's hallmark eventse that cause the condition to worsene. Every time a host cell that causes tissue injurye comes into contact with the host, the host generates an excessively inefficient pro-inflammatory responsee. They can cause cell death through phagocytosis, apoptosis, or trogocytosise (the absorption of livinge cells), which may be cruciale for immune evasion, as well as othere detrimental effects that are brought on by their attachment to the host cellse. Immune evasion techniquese are used by Eh to survive and induce diseasee manifestation in the host; these techniquese are the main focuse of this reviewe. eAn estimated 100,000 individualse are predicted to die eache year from E. histolytica infectione, which is thoughte to impact 1% of peoplee. Clinicale manifestations of a mebice infection can range frome mild to severee, causing extraintestinal abscessese and diarrhea. Onlye 20% of those whoe are affectede, like othere infectious diseasese, reportedly exhibite symptoms. The outcomee of an infection is controllede by both the genetic makee-up of the parasitee and the host ase well as environmental factors like the microbiome. Amebic infection goes through a number of critical stages, includinge the degeneratione of the mucosale layer and infiltratione into it, adherencee to the intestinal epitheliume, invasion intoe the tissuese, and diffusione to other organs.